Charismatic Leadership And Organizational Commitment Influence On Employee Performance In Medan City Government - Karim, Ahmad (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study is to determine how the influence of charismatic leadership on employee performance, organizational commitment to employee performance, and together charismatic leadership and organizational commitment to employee performance in Medan City Government. The research method was conducted using quantitative analysis using a sample of 80 Medan City Government employees. The results of the study are: Charismatic leadership does not have a significant effect on employee performance in Medan City Government. It demonstrates charismatic leadership through dimensions: vision and articulation, personal risk, sensitivity to the environment, sensitivity to members, behavior outside the rules, and capacity to be unable to respond. Organizational commitment has a significant effect on the performance of employees in the Medan City Government. The magnitude of the influence of organizational commitment on employee performance is 68.8%. This shows that organizational commitment with the dimensions of Affective Commitment, Sustainability Commitment, and Normative Commitment is able to reflect organizational commitment in influencing employee performance. Charismatic leadership and organizational commitment together have a significant effect on employee performance in Medan City Government by 63.8%. While the remaining 36.2% was influenced by other variables that were not included in the research model. It can be explained that charismatic leadership and organizational commitment together can significantly improve employee performance. This means that employees in the Medan City Government in improving performance can make joint efforts with leaders and subordinates to improve charismatic leadership and organizational commitment.